2001
DOI: 10.1063/1.1406976
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical coexistence of phases in molecular clusters

Abstract: The effect of ions on solid-liquid phase transition in small water clusters. A molecular dynamics simulation study Two solid structures, a bcc orientationally disordered phase and a strained monoclinic orientationally ordered phase, may coexist for clusters of octahedral molecules. However, this coexistence is more difficult to observe in computer simulations of SF 6 clusters than of TeF 6 clusters although the SF 6 and TeF 6 molecules have the same symmetry. This study finds why this difference occurs. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
(34 reference statements)
1
21
0
Order By: Relevance
“…As pointed out by Berry [33], a rugged potential energy surface requires a slow enough change of the system's temperature to avoid trapping it in a metastable state. If this trapping happens, the system cannot escape from a local minimum for realistic computational times.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by Berry [33], a rugged potential energy surface requires a slow enough change of the system's temperature to avoid trapping it in a metastable state. If this trapping happens, the system cannot escape from a local minimum for realistic computational times.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the melting transition for Lennard-Jones clusters has been described [2][3][4][5] as an equilibrium between solidlike and liquidlike forms of the system. Other CPTs have also been identified that resemble transitions occurring in bulk, e.g., order-disorder, 6,7 orientational, 8 and configurational transitions. 9 In many of the above studies, 3-7 the computational characterization of these transitions has been made by identifying anomalies in the heat capacity as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…1 From a computational point of view, one of the most addressed issues associated with clusters is the so-called cluster phase transitions ͑CPTs͒. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] It has been recognized that CPTs differ from phase transitions in bulk in that these transitions due not occur at a given temperature but rather in a temperature range where isomeric forms of the cluster with considerable difference in energy coexist. For example, the melting transition for Lennard-Jones clusters has been described [2][3][4][5] as an equilibrium between solidlike and liquidlike forms of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Clusters made of TeF 6 molecules have rugged PES [8]. Such a PES contains many minima separated by high barriers that hamper the expected evolution of the system at a given temperature.…”
Section: Introductionmentioning
confidence: 99%
“…If this happens, one gets biased values of the time-averaged quantities such as internal energy or entropy. Increasing the time of computations is a possible solution to this problem, however, one should not forget that very long runs violate the energy conservation even in the most efficient integration schemes, like simplex method [8]. 'Violation' means that if the same computation is performed with t replaced with (Àt) the trajectory will not return to its initial point in the phase space.…”
Section: Introductionmentioning
confidence: 99%